PERILAKU IBU PASCA PERSALINAN TENTANG MANFAAT OUKUP DI KLINIK DAMAI YANTI TAHUN 2018 - Debora Paninsari (Universitas Prima Indonesia, 2018)
Adequate traditional medicine originating from the Karoness tribe that utilizes the diversity of plant species as ingredients for health after childbirth and treatment of various types of diseases. Medicines in the Karoness community and continue to grow and demand by the community to cure various types of diseases. Oukup is a traditional treatment from the Karo tribe for health during childbirth, good body care will restore maternal health and beauty as before pregnancy. Steam bath or adequate is the most appropriate tool to overcome the excess serum in the body and can improve nerve alignment and muscles. The purpose of this study is to find out about the description of postpartum maternal behavior about adequate benefits at Yanti Peace Clinic in 2018. This type of research is descriptive using an observational approach. Descriptive research is research conducted on a set of objects that aim to see a picture of something that happens in a particular population. The sample used was 6 postpartum mothers at Yanti Peace Clinic in 2018. The results of this study obtained from 6 respondents who had good behavior as much as 1 respondent (17%), and who had enough knowledge as much as 2 respondents (33%), and those who lacked 3 respondents (50%). The conclusion that is obtained is that the description of postpartum maternal behavior about adequate benefits at the Yanti Peace Clinic in 2018 is still lacking. Suggestions for respondents to find out more about information about adequate benefits and to health workers to provide information to the community.